2022
DOI: 10.1007/s11606-022-07490-9
|View full text |Cite
|
Sign up to set email alerts
|

Innovation and Missed Opportunities in Internal Medicine Undergraduate Education During COVID-19: Results from a National Survey

Abstract: BACKGROUND: COVID-19 disrupted undergraduate clinical education when medical schools removed students from clinical rotations following AAMC recommendations. Clerkship directors (CDs) had to adapt rapidly and modify clerkship curricula. However, the scope and effects of these modifications are unknown. OBJECTIVE: To examine the effects of the initial phase of COVID-19 on the internal medicine (IM) undergraduate clinical education. DESIGN: A nationally representative web survey. PARTICIPANTS: IM CDs from 137 LC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…In the United States, results from national survey of all medical schools with regards to the internal medicine exposure during Covid 19 pandemic showed that bedside teaching and physical examination activities were "let go" during this period and students were not allowed from direct patient care. [32] This was also adapted by the UST-FMS for the medical clerks in the emergency room settings, ambulatory care, endoscopy, pulmonary and dialysis units/.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the United States, results from national survey of all medical schools with regards to the internal medicine exposure during Covid 19 pandemic showed that bedside teaching and physical examination activities were "let go" during this period and students were not allowed from direct patient care. [32] This was also adapted by the UST-FMS for the medical clerks in the emergency room settings, ambulatory care, endoscopy, pulmonary and dialysis units/.…”
Section: Discussionmentioning
confidence: 99%
“…In the same USA national survey, most students agreed that the pandemic had definitely disrupted their internal medicine direct patient exposure, and even stated that they should continued with normal clinical exposures during this pandemic even to accept the risk of infection with COVID-19 if they returned to the clinical setting [32].…”
Section: Discussionmentioning
confidence: 99%
“…This lack of effect on NBME subject exam performance has also been previously described for other subject examinations [ 12 ]. The study by Alexandraki et al also suggests that shortened IM clerkship time due to COVID-19 closures did not objectively affect exam performance on the NBME Medicine subject exam [ 13 ]. However, it did have other effects on medical students as they struggled to see the required clinical experiences and diversity of cases during the shortened time period.…”
Section: Discussionmentioning
confidence: 99%
“…Purpose: As educators in undergraduate medical education, we seek to maximize student learning, grading transparency and fairness, and provide useful information to residency programs that support continued professional development. In recent years medical schools have encountered disruptions to curricular and assessment operations, in part due to the impacts of COVID-19 1 and the change to a pass/fail-scored United States Medical Licensing Examination (USMLE) Step 1. Medical schools have also developed an increased awareness of long-standing systemic inequities in the grading of nonmajority racial groups.…”
mentioning
confidence: 99%